2021
DOI: 10.1021/acs.est.1c03071
|View full text |Cite
|
Sign up to set email alerts
|

New Technologies Can Cost Effectively Reduce Oil and Gas Methane Emissions, but Policies Will Require Careful Design to Establish Mitigation Equivalence

Abstract: Reducing methane emissions from oil and gas systems is a central component of US and international climate policy. Leak detection and repair (LDAR) programs using optical gas imaging (OGI)-based surveys are routinely used to mitigate fugitive emissions or leaks. Recently, new technologies and platforms such as planes, drones, and satellites promise more cost-effective mitigation than existing approaches. To be approved for use in LDAR programs, new technologies must demonstrate emissions mitigation equivalent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 36 publications
2
26
0
Order By: Relevance
“…In recent years, a range of potential detection and/or measurement technologies have been explored with promise to significantly reduce time and labour costs to find and measure sources of methane, especially for applications in the oil and gas sector (Bell et al, 2020;Fox et al, 2019;Kemp and Ravikumar, 2021;Rashid et al, 2020;Ravikumar et al, 2019;Schwietzke et al, 2019). Of particular interest are airplane-mounted technologies, which are increasingly used in large-scale field campaigns with success (Chen et al, 2022;Cusworth et al, 2021;Tyner and Johnson, 2021) and gaining acceptance in alternate fugitive emissions management programs (Alt-FEMP) replacing or supplementing optical gas imaging (OGI) surveys using hand-held infrared cameras (AER, 2021;Bridger Photonics, 2022;InvestableUniverse, 2021;Kairos Aerospace, 2022a).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a range of potential detection and/or measurement technologies have been explored with promise to significantly reduce time and labour costs to find and measure sources of methane, especially for applications in the oil and gas sector (Bell et al, 2020;Fox et al, 2019;Kemp and Ravikumar, 2021;Rashid et al, 2020;Ravikumar et al, 2019;Schwietzke et al, 2019). Of particular interest are airplane-mounted technologies, which are increasingly used in large-scale field campaigns with success (Chen et al, 2022;Cusworth et al, 2021;Tyner and Johnson, 2021) and gaining acceptance in alternate fugitive emissions management programs (Alt-FEMP) replacing or supplementing optical gas imaging (OGI) surveys using hand-held infrared cameras (AER, 2021;Bridger Photonics, 2022;InvestableUniverse, 2021;Kairos Aerospace, 2022a).…”
Section: Introductionmentioning
confidence: 99%
“…Here, two different sources of emissions based on field data were combined to have a representative emission distribution of the Permian basin. The first dataset came from studies using close range inspections (OGI cameras or method 21) from Allen et al, 7 Bell et al 21 and Kuo et al, 22 as described by Kemp et al 13 with the addition of data from Pacsi et al 23 These studies were chosen as they have information of the equipment where each emission originated from, which was used to randomly assign emissions in this study from that equipment category, for example a component at a separator will sample from the emissions originating from separators from the combined datasets. The second dataset was from Permian basin flyovers from Bridger Photonics, whose distribution is shown in Figure 1 and was also disaggregated by equipment.…”
Section: Emission Measurementsmentioning
confidence: 99%
“…14 Bridger Photonics uses a continuous wave LiDAR measurements and has been described and evaluated by Johnson et al 24 and Conrad et al 25 From this dataset, only the emissions where operators confirmed that the source was non-routine, after following-up, were included in the distribution. Sensitivity analysis S0 was performed by adding to the distribution of close range inspections data from ERG 26 and Ravikumar et al, 27 as described by Kemp et al, 13 and assigning emissions randomly from a combined distribution, independently of which equipment the data came from, except for tanks and flares where the data comes from the flyover distribution.…”
Section: Emission Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regression results for stages 1 and 2 based on the fixed-intercept ordinary least squares regression in Eq (1)…”
mentioning
confidence: 99%